The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 26 Night duty should not be permitted until after one year in hospital. Night duty should be limited to three months, and there should be on interval of not less than three months before it is again resumed. (4) OFF DUTY. The nurse should have not less than one full day a week, and one weekend a month. (5) HOLIDAYS. The annual holiday should be not less than three weeks. (6) MEALS. Not less than 45 minutes should be allowed for dinner, and half-an-hour for each other meal. Nurses on night duty should not take meals in the wards. (7) LIVING ACCOMMODATION. Each nurse should have a separate bed-room with suitable amenities with respect to rest-room, recreation-room, bath-room, and lavatories. A special block of bed-rooms should be provided for nurses on night duty so that rest may be secured. (8) ACCESS TO A DOCTOR. In case of indisposition the nurse should have free, direct, and immediate access to one of the hospital doctors available daily for this purpose, and sisters and matrons should encourage nurses to seek prompt attention. (9) SALARIES. Salaries during training should be sufficient to meet all needs, including holidays, and at present £40 should be the minimum. (10) POSTING OF NOTICES. All rules and regulations should be posted in a conspicuous place. (11) UNIFORM. The uniform now worn by nurses has been little modified for many years past. The tight bodices, long full skirts, stiff collars and cuffs and elaborate head-dresses were an improvement on women's dress at the time when they were adopted; but in this the authorities have not kept pace with modern ideas of hygiene and comfort. We suggest that uniform should be reconsidered and designs adopted more in accordance with the comfortable dress now worn by women in other employments. REGISTRATION. Registration should be compulsory. CONDITIONS OF EMPLOYMENT OF FULLY TRAINED NURSES The problem of the conditions of employment for nurses when trained is complicated, because the nurses work under widely different conditions. Employers, however, can be divided into three main classes: — i. Committees of institutions of a voluntary kind. ii. Committees of public authorities. iii. Private individuals. 126/TG/RES/X/1036A/14